2011
DOI: 10.1371/journal.pone.0016841
|View full text |Cite
|
Sign up to set email alerts
|

miR-155, a Modulator of FOXO3a Protein Expression, Is Underexpressed and Cannot Be Upregulated by Stimulation of HOZOT, a Line of Multifunctional Treg

Abstract: MicroRNAs (miRNAs) play important roles in regulating post-transcriptional gene repression in a variety of immunological processes. In particular, much attention has been focused on their roles in regulatory T (Treg) cells which are crucial for maintaining peripheral tolerance and controlling T cell responses. Recently, we established a novel type of human Treg cell line, termed HOZOT, multifunctional cells exhibiting a CD4+CD8+ phenotype. In this study, we performed miRNA profiling to identify signature miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 44 publications
3
33
1
Order By: Relevance
“…One signaling pathway that is targeted at multiple levels by mir-155 (15,25,26), and could reasonably account for the defect observed, is the PI3K/Akt signaling cascade. We isolated CD8 + T cells from WT and 155KO mice and stimulated them with anti-CD3 for 30 min in vitro.…”
Section: Mir-155 Promotes T Cell Survival Via Aktmentioning
confidence: 98%
See 1 more Smart Citation
“…One signaling pathway that is targeted at multiple levels by mir-155 (15,25,26), and could reasonably account for the defect observed, is the PI3K/Akt signaling cascade. We isolated CD8 + T cells from WT and 155KO mice and stimulated them with anti-CD3 for 30 min in vitro.…”
Section: Mir-155 Promotes T Cell Survival Via Aktmentioning
confidence: 98%
“…Mice lacking mir-155 have a multitude of immune defects, including impaired germinal center formation (11,12), CD4 + T cell function, regulatory T (Treg) cell development, and homeostatic expansion (13)(14)(15). The defects observed in the CD4 + T cell population include a Th2-skewing bias (11,12,16) as well as an inability to produce functional Th17 cells leading to resistance to the induction of experimental autoimmune encephalomyelitis (17,18) and experimental rheumatoid arthritis (9,19).…”
Section: Cd4mentioning
confidence: 99%
“…Recent evidence has suggested that miR-155 can regulate the development of Tregs (35,36). Therefore, we investigated whether APCs including DCs, macrophages, and B cells were critical for the proliferation of Tregs in vivo (35, 37-39) and were involved in the development of ALI (27,40).…”
Section: Macrophages Dominantly Induced the Proliferation Of Tregsmentioning
confidence: 99%
“…142 As Foxp3 is proposed to upregulate miR-155 expression by inducing its resident gene, and FOXO3a is a positive regulator of Foxp3 expression, this could provide a negative feedback of Foxp3 expression through miRNAs. Other studies have found that miR-142-3p can regulate adenyl cyclase 9 mRNA and the subsequent production of cAMP in Treg cells.…”
mentioning
confidence: 99%